2019
DOI: 10.31234/osf.io/cvpuw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multi-Lab Test of the Facial Feedback Hypothesis by The Many Smiles Collaboration

Abstract: The facial feedback hypothesis suggests that an individual’s subjective experience of emotion is influenced by their facial expressions. Researchers, however, currently face conflicting narratives about whether this hypothesis is valid. A large replication effort consistently failed to replicate a seminal demonstration of the facial feedback hypothesis, but meta-analysis suggests the effect is real. To address this uncertainty, a large team of researchers—some advocates of the facial feedback hypothesis, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Interestingly, this problem seems difficult to overcome even when researchers make a concerted effort to reconcile their disagreements (Coles et al, 2019), suggesting that theoretical models are not specified clearly enough for the adversaries to see where their assumptions diverge.…”
Section: Are Psychologists Ready To Test Hypotheses?mentioning
confidence: 99%
“…Interestingly, this problem seems difficult to overcome even when researchers make a concerted effort to reconcile their disagreements (Coles et al, 2019), suggesting that theoretical models are not specified clearly enough for the adversaries to see where their assumptions diverge.…”
Section: Are Psychologists Ready To Test Hypotheses?mentioning
confidence: 99%
“…Importantly, meta-analysis reveals that facial feedback exerts a small impact on emotional experience (Coles, Larsen, & Lench, 2019). For example, previous research has indicated that posing smiles can both magnify ongoing feels of happiness and initiate feelings of happiness in otherwise nonemotional scenarios (Coles, March, et al, 2019).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Another large-scale collaboration in psychology is the Many Smiles Collaboration, which focuses on human facial expressions with the goal of testing the facial feedback hypothesis (Coles et al, 2019). The ManyBabies consortium (Frank et al, 2017), another example of a large-scale collaboration in psychology, conducts replications of influential experiments in developmental psychology focusing on human infants.…”
Section: Large-scale Collaboration In Psychologymentioning
confidence: 99%